METHODS OF IMPROVING PEDAGOGICAL SKILLS OF OFFICERS - Cобиров Ботиржон Тохиржонович (Galaxy International Interdisciplinary Research Journal, 2023)
In this article , one of the important components of the pedagogical skills of an officer is the period of manifestation of pedagogical ability and the issues of proper organization of the processes of effective organization of pedagogical activities are extensively covered.